Impacts of the 2011 tsunami on the subtidal polychaete assemblage and the following recolonization in Onagawa Bay, northeastern Japan. (December 2015) - Abe, Hirokazu; Kobayashi, Genki; Sato-Okoshi, Waka
Abstract: The ecological impacts of the 2011 Great East Japan Earthquake and tsunami and the following recolonization of the subtidal benthic polychaete community were examined by monthly pre- and post-quake field surveys that were conducted in Onagawa Bay from 2007 to 2013. Before the tsunami, the species composition in this benthic community was constant and was dominated by cirratulid and magelonid polychaetes. The density and biomass of benthic polychaetes drastically decreased after the tsunami, and the polychaete community fluctuated during the 2 years after the natural disaster. Spionid and capitellid polychaetes were dominant at this period. In June 2013, the community entered a new constant stage dominated by maldanids, which is different from the pre-quake community. Ecological impacts due to chemical pollution were suggested in addition to the tsunami disturbance. These overlapping effects and physical, chemical and biological factors affected the recovery and recolonization of the polychaete community after the natural disaster. Highlights: Impacts of earthquake and tsunami on benthic polychaete community were examined. Following recolonization of the polychaete community after tsunami was revealed. Polychaete community fluctuated during the 2 years after the natural disaster. Polychaete community entered a new constant stage two years after the disturbance. Drastic changes in dominant taxa occurred after the tsunami.